Correlation of learning motivation and emotional intelligence with student higher order thinking skills level on biology material - Wahdania Misliyanti; Nurhayati B.; A. Mushawwir Taiyeb (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2024)
The ability to think at a high level is essential for students to master because this ability encourages students' motivation to look at every problem critically. Learning motivation and emotional intelligence are several factors that determine how students have the desire or drive to achieve their goals. This study is ex post facto research to examine the relationship between learning motivation and emotional intelligence with higher-order thinking skills. The population in this study were all students of grade XI IPA at public senior high schools in the Majene district of the 2023/2024 academic year. The research samples 268 students by employing a simple random sampling technique with representatives of one school for each sub-district in Majene Regency. The research instruments were a questionnaire on learning motivation and emotional intelligence and a test of higher-order thinking skills on Biology learning material. The data obtained in this research was analyzed using descriptive and inferential statistics (multiple and simple regression analysis) with the help of the SPSS program. Based on the hypothesis testing, the research results reveal that learning motivation and emotional intelligence have a very strong and significant relationship to higher-order thinking skills. Further research is needed to achieve broader goals, increase learning motivation and increase students' positive character values.Abstrak. Kemampuan berpikir tingkat tinggi sangat penting untuk di kuasai oleh peserta didik, karena kemampuan tersebut mendorong motivasi peserta didik untuk memandang setiap permasalahan dengan kritis. Motivasi belajar dan kecerdasan emosional merupakan beberapa faktor yang menjadi penentu bagaimana peserta didik memiliki keinginan atau dorongan dalam menggapai cita-citanya. Penelitian ini adalah penelitian ex post facto yang bertujuan untuk mengetahui hubungan antara motivasi belajar dan kecerdasan emosional dengan keterampilan berpikir tingkat tinggi. Populasi dalam penelitian ini adalah seluruh peserta didik kelas XI IPA SMA Negeri di Kabupaten Majene tahun ajaran 2023/2024. Sampel dalam penelitian ini diambil sebanyak 268 dengan menggunakan teknik simple random sampling dengan perwakilan satu sekolah untuk masing-masing kecamatan yang ada di Kabupaten Majene. Instrumen penelitian ini adalah angket motivasi belajar dan kecerdasan emosional dan tes keterampilan berpikir tingkat tinggi pada materi biologi. Data yang diperoleh dalam penelitian ini di analisis menggunakan statistik deskriptif, dan inferensial (analisis regresi ganda dan sederhana) dengan bantuan program SPSS. Berdasarkan pengujian hipotesis, hasil penelitian menunjukkan bahwa motivasi belajar dan kecerdasan emosional memiliki hubungan yang sangat kuat dan signifikan terhadap keterampilan berpikir tingkat tinggi. Penelitian lebih lanjut diperlukan untuk mencapai tujuan yang lebih luas meningkatkan motivasi belajar dan meningkatkan nilai karakter positif siswa.